Trabalho docente e ensino : um estudo sobre didáticas críticas, utilizando ambiente virtual de aprendizagem, com professores da rede pública estadual de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This Dissertation discusses how different critical perspectives of didactics—namely, Developmental, Intercultural, and Complex—can contribute to the epistemological foundations of basic education teachers in their teaching work. The research is part of the research line "Initial and Continuing Teacher Education Processes in Different Educational Contexts" within the Graduate Program in Science Teaching at the State University of Goiás. The study seeks to understand the relationships and relevance, based on a framework by Ilma Passos Alencastro Veiga (2015), of the various critical epistemologies of didactics in the teaching and learning process, as well as the importance of the teaching profession in educational practice. The research is justified by the growing need for continuing teacher education in basic education, considering the profound changes and capitalist influence in the contemporary world and its close relationship with the current configuration of Brazilian education and its public policies. Furthermore, it highlights the necessity of fostering didactic-pedagogical processes in schools and deepening studies on critical didactics in basic education, especially in the early 21st century. This qualitative research is based on the action-research- formation method, as proposed by David Tripp (2005), which aims to understand these relationships and their relevance in pedagogical and didactic aspects. Content analysis by Laurence Bardin (2009) was also adopted as a methodological approach, providing theoretical support for our methodological approach, which describes the phenomenon to understand it based on the representations of the participants through their responses and shared experiences. The primary data collection strategy was offering a course on Critical Didactics, in addition to administering questionnaires with objective, semi-open, and discursive questions to the participating teachers. As an educational product associated with the research, a Virtual Learning Environment (VLE) was developed and implemented using the MOODLE Learning Management System. The system was customized to meet the research's goals and was named AVAPROF (Virtual Learning Environment for Teachers). AVAPROF is available online at www.avaprof.com.br. In addition to AVAPROF, a 40-hour course on the perspectives of the mentioned didactics was created. The course was offered through AVAPROF to teachers and other basic education professionals in the public school system of the State of Goiás from March to July 2024. As the main results, it was observed that most teachers initially perceived didactics only as a methodology or technique applied in their practices. However, as the participants progressed through the training course, changes in response patterns were noted, aligning more closely with the critical perspectives of the didactics presented. In summary, the research indicated that the professionalism of the basic education teachers, who participated in the study, is largely developed from a technicist and traditional didactic perspective. Furthermore, the research pointed out that there is room for the development of more critical thoughts and practices, which can be fostered through more reflective and critical training experiences, such as the one proposed in this study, allowing them access to different epistemologies.
Teaching work and education : a study on critical didactics using a virtual learning environment with public school teachers in the state of Goiás
Keywords: Educação; Didáticas críticas; Trabalho docente; Formação de professores; Ambiente virtual de aprendizagem; Education; Critical didactics; Teaching work; Teacher training; Virtual learning environment.; CIENCIAS EXATAS E DA TERRA::FISICA